2021
DOI: 10.1515/ntrev-2021-0047
|View full text |Cite
|
Sign up to set email alerts
|

Review on resistive switching mechanisms of bio-organic thin film for non-volatile memory application

Abstract: Bio-organic, as one of the sustainable and bioresorbable materials, has been used as an active thin film in producing resistive switching random access memory (RRAM) due to its specialized properties. This type of nonvolatile memory consists of a simple unit structure with the processed and solidified bio-organic-based thin film sandwiched between two electrodes. Its memory characteristics are significantly affected by the resistive-switching mechanism. However, to date, the reported mechanisms are very divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 93 publications
0
48
0
Order By: Relevance
“…Changes in the 10-mV range have been reported for biomolecules adsorbed on different surfaces and forming thin layers [ 58 ]. The carrier conduction process depends on the work function differences of LTO and graphene and LUMO and HOMO of the PLL thin film [ 59 ], suggesting a conductivity change in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the 10-mV range have been reported for biomolecules adsorbed on different surfaces and forming thin layers [ 58 ]. The carrier conduction process depends on the work function differences of LTO and graphene and LUMO and HOMO of the PLL thin film [ 59 ], suggesting a conductivity change in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the slope at region A, it can be concluded that either a trap‐fill limited and/or a trap‐free conduction mechanism dominates in the low voltage region. [ 6,15 ] It is highly possible that due to the incorporation of C60, carriers can be consistently trapped by C60 and contributed to a higher resistance with a less steep slope as shown in region A. At higher voltages in region B, the conduction of carriers is governed by a trap‐fill limited conduction mechanism, which is similar to carrier conduction in the bulk polymannose thin film without C60.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, an interlocking effect of C60 with polymmanose may contribute to the reduction of V SET as the concentration of C60 increases. It is unlikely that the conductive paths are metallic as the formation of these metallic filaments must be initiated by a redox reaction from TE, [ 6,16 ] but in this work an inert electrode was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior allows the use of these devices for the implementation of artificial neuronal synapses in neuromorphic systems, since the synaptic weight between two neurons can be electrically adjusted [5]. Various materials have been studied as resistive switching devices, such as perovskites [6], manganites [7], and even organic materials [8]. However, metal oxides are the most widely studied materials [9].…”
Section: Introductionmentioning
confidence: 99%